Land[e]scapes - Pericleous, Vicky (My University, 2023)
Art Seen is pleased to present the off-site group exhibition 'Land[e]scapes' taking place in Limassol on view for only two days October 21 and October 22, 2023. A visual journey that traverses the realms of topos, geology, and time titled 'Land[e]scapes'. Curated to invite viewers to engage in a thoughtful exploration of our relationship with the landscape. Featuring a selection of artists including Panayiotis Andreou, Marina Genadieva, Vicky Pericleous, Nicos Philippou & Marilena Zackheos, Amy Stephens, Vassia Vanezi and Vasilis Zografos whose creations transcend conventional boundaries and awaken new realms of contemplation. The exhibition 'Land[e]scapes' is presented within the framework of Limassol Art Walks in a pop-up space in Limassol at Cassina - El Greco showroom Eleftherias Street 139-141, 3042 Limassol
Keywords: Arts